From Port Hope to Thunder Bay: Joseph Goodwin King, the Canadian Pacific Railway and Western Canada’s first grain elevator on the Great Lakes 1883-1910 - Scollie, F. (Ontario History, 2022)
The career of Joseph Goodwin King (1844-1910), grain elevator operator at Port Hope and Port Arthur, Ontario, sheds light on many aspects of Canadian agricultural and economic history— the role of railway companies in the grain trade, the decline of Lake Ontario grain ports, the rise of Thunder Bay on Lake Superior as the major Canadian grain port for western Canada, as well as improvements in North American grain cleaning and drying methods, and grain elevator construction.